Problems and Solutions of Teaching English in Non-Philological Universities (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Teaching English in non-philological universities presents unique challenges due to the diverse linguistic backgrounds and varied academic goals of students. This article examines the prevalent issues encountered in such settings and proposes effective solutions to address them. By exploring innovative teaching methodologies, fostering a supportive learning environment, and leveraging technology, educators can enhance English language proficiency among students, thereby promoting academic success and global competence.